DISORGANISASI PENERAPAN PSBB DI DKI JAKARTA SEBAGAI REFLEKSI KOMPLEKSITAS RELASI PEMERINTAH PROVINSI DKI JAKARTA DAN PEMERINTAH PUSAT - Faiz Rafiza Ahmadani Rafi Aquary (Muhammadiyah Law Review Journal, 2022)
Large-scale social restrictions or PSBB have brought up immense multidimensional effects within the Indonesian political landscape. One of the things which could be dissected from this regard would be in the governance system. In this sense, one might take a look at the current management of the COVID-19 pandemic within the Province of Special Capital Region of Jakarta. In this province, the Indonesian central government has often „collided‟ with the province‟s regional government; which ranging from issues such as social assistance, transportation, economic, and also law enforcement. The impact of such „skirmish‟ has taken its toll on all of the city‟s residents; but most importantly hit it the hardest for the city‟s poorest and most vulnerable group. With this in mind, the goal of this paper is to broaden the knowledge within the issue of pandemic management, especially within the Indonesian context. Besides, it also strives to find out several recommendations which should be taken by the government in order to „solve‟ this issue as comprehensively as possible.